2012
DOI: 10.1002/hec.2842
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Patients Having Coronary Artery Bypass Grafts Have Different Costs or Length of Stay? An Analysis Across 10 European Countries

Abstract: We analyse variations in cost or length of stay (LoS) for 66 587 patients from 10 European countries receiving a coronary artery bypass graft (CABG) procedure. In five of these countries, variations in cost are analysed using log-linear models. In the other five countries, negative binomial regression models are used to explore variations in LoS. We compare how well each country's diagnosis-related group (DRG) system and a set of patient-level characteristics explain these variations. The most important explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…21 The EuroDRG research group classified 10 encounter types by 11 DRG algorithms and found significant variation across countries. 22-25 Continued analysis of how well DRGs predict actual patient care is required to ensure that DRGs adequately reflect patient characteristics and treatments in both pediatric and adult admissions, particularly in light of recent incorporation of ICD-10-CM codes. Although the Centers for Medicare and Medicaid Services predicts minimal impact on overall payments as DRG algorithms change from ICD-9-CM to ICD-10-CM codes, there may be a varying impact at the hospital level.…”
Section: Discussionmentioning
confidence: 99%
“…21 The EuroDRG research group classified 10 encounter types by 11 DRG algorithms and found significant variation across countries. 22-25 Continued analysis of how well DRGs predict actual patient care is required to ensure that DRGs adequately reflect patient characteristics and treatments in both pediatric and adult admissions, particularly in light of recent incorporation of ICD-10-CM codes. Although the Centers for Medicare and Medicaid Services predicts minimal impact on overall payments as DRG algorithms change from ICD-9-CM to ICD-10-CM codes, there may be a varying impact at the hospital level.…”
Section: Discussionmentioning
confidence: 99%
“…Separate multivariable logistic regressions were analyzed, with the following events defined as outcomes: combined complications, cardiac complications, pulmonary complications, invasive ventilation, transfusion, and use of ICU services. To determine the association between type of anesthesia and length of stay, we performed a multivariable negative binomial regression, which is recommended for discrete outcomes when overdispersion (variance [ mean) is present [2] and has been used previously in health research for this purpose [6,8,16].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis reveals the wide variation that persists in the number of categories patients are grouped into. It should also be noted that having a larger number of groups does not necessarily result in a more accurate reflection of the variation in cost of CABG patients [10], the variation in the particular variables used to define the boundaries of DRGs and how these are hierarchically structured is also important. The decision as to the weight attached to particular variables is also explored, drawing particular attention to the different ways that the same characteristic can be dealt with and the impact this has on reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…This work is performed within the framework of the EuroDRG b project, which looks at hospitalisations for ten conditions, analysing the ability of different DRG systems to account for patient characteristics, as well as analysing the impact of a variety of patient characteristics upon the cost or length of stay of patients [10,11]. In this article we focus on CABG surgery, as one of the most frequently performed major surgical procedures and a procedure with many variations in approach.…”
Section: Introductionmentioning
confidence: 99%